The ’’Hanging Maneuver’’ Technique during Pancreaticoduodenectomy: The Result of a Technical Evolution to Approach the Superior Mesenteric Artery - Marzano, Ettore; Piardi, Tullio; Pessaux, Patrick (JOP. Journal of the Pancreas, 2011)
No abstract available. Image: “Hôpital de Hautepierre”. Strasbourg, France.